PENGARUH VARIABEL-VARIABEL KARAKTERISTIK ANGGARAN TERHADAP EFEKTIFITAS PELAKSANAAN ANGGARAN PADA PT. (PERSERO) PELABUHAN INDONESIA III - Agus Sunaryo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
PT. (PERSERO) Indonesia III Harbour as the one of corporate with persero form have the way to look for profit oriented, so that’s management must do one integration plan in one form of plan work and corporate budged (RKAP). For getting the optimal plan work and corporate budged who if RKAP must be the way of control of corporate in short way (annual). One factor to do RKAP can be effective is needs participate do budged in RKAP form process. The qualitative relation use for know the factors who control of effectiveness budged. They one production factor in budged form. From data that we know if the participate factor in budged form have a dominant control to do effectiveness of budged (X1) have dominant relation, this thing is known from the signify 0,031, but the dominant control is = 0,05 or smaller than 0,05. The less dominant variables is the difficulty of budged (X2), the divulge of highness management (X3), and budged department (X4) where the significant up to 0,05. With that research it is hoped that it can be ingredients to management to increase have the participate of budged in budged form process, that can be increase through the effectiveness of budged.